2001
DOI: 10.1021/jm0101444
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structures of Candida albicans Dihydrofolate Reductase:  High Resolution Ternary Complexes in Which the Dihydronicotinamide Moiety of NADPH Is Displaced by an Inhibitor

Abstract: X-ray crystallographic analysis of 5-(4'-substituted phenyl)sulfanyl-2,4-diaminoquinazoline inhibitors in ternary complex with Candida albicans dihydrofolate reductase (DHFR) and NADPH revealed two distinct modes of binding. The two compounds with small 4'-substituents (H and CH3) were found to bind with the phenyl group oriented in the plane of the quinazoline ring system and positioned adjacent to the C-helix. In contrast, the more selective inhibitors with larger 4'-substituents (tert-butyl and N-morpholino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Many MTX derivatives have been described that also seem to trend toward extended aliphatic extensions, but these compounds lack structural data for direct threedimensional comparison (36,42,43). Interestingly, some Plasmodium and Candida structures, which are considerably different from the B. anthracis enzyme, contain inhibitors, as well as a fortuitous buffer molecule (MES) in a position roughly equivalent with the linker-dihydrophthalazine portion of RAB1 (PDB ID code 2BLB) (37,48) (Fig. 5F), indicating unoccupied volume within the binding site complexed with those inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Many MTX derivatives have been described that also seem to trend toward extended aliphatic extensions, but these compounds lack structural data for direct threedimensional comparison (36,42,43). Interestingly, some Plasmodium and Candida structures, which are considerably different from the B. anthracis enzyme, contain inhibitors, as well as a fortuitous buffer molecule (MES) in a position roughly equivalent with the linker-dihydrophthalazine portion of RAB1 (PDB ID code 2BLB) (37,48) (Fig. 5F), indicating unoccupied volume within the binding site complexed with those inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among the hydroxysteroid dehydrogenases belonging to the SDR family, 17␤-HSDs are attractive targets for structure-based rational drug design for the prevention and control of sex steroid-dependent cancers and 11␤-HSD1 is another good target for drug design for the therapy of several metabolic syndromes (insulin resistance, hyperlipidemia, arterial hypertension, and obesity). A recent study showed that two highly selective inhibitors can occupy the dihydronicotinamide binding site and thus displace the dihydronicotinamide moiety in dihydrofolate reductase (35). Also, in 3␣,20␤-hydroxysteroid dehydrogenase, a member of the SDR family, the hemisuccinate side chain of the inhibitor, carbenoxolone, makes a hydrogen bond with the hydroxyl group of the conserved residue Tyr 152 and occupies the position of the nicotinamide ring of the cofactor (36).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Although known clinical drugs against DHFR show weak activity against C. albicans, [5] potent, selective inhibitors of C. albicans DHFR have been reported. [6,7] Their selectivity for C. albicans versus human DHFR has been ascribed in part to differences in protein-ligand hydrogen bonding. Such differences can be detected by analysis of the protein electrostatic potentials.…”
mentioning
confidence: 99%